Pengaruh Ulasan Online dan Kualitas Pelayanan Terhadap Keputusan Tamu Menginap di Goya Boutique Resort Ubud - Yanti, Ni Wayan Novi; Antari, Ni Luh Sili; Yogantara, Komang Krishna (Jurnal Mosaik Hospitaliti, 2023)
The research entitled: Effect of Online Reviews and Service Quality on Guest Decisions to Stay at Goya Boutique Resort Ubud Bali aims to determine the effect of online reviews and service quality on guest decisions to stay at Goya Boutique Resort Ubud Bali and to find out which variables have a dominant influence on guest decisions. stay at Goya Boutique Resort Ubud Bali either partially or simultaneously. Determination of the sample size of respondents using the Solvin formula, so only 95 respondents were used in this study. Meanwhile, data processing using SPSS with multiple regression analysis techniques where the results show that online reviews and service quality have a significant positive influence either partially or simultaneously on the decision of staying guests. The results are based on the results of the T-test that the calculated T value is greater than the T table value so it can be concluded that there is a partially significant effect between Online Reviews on Staying Guest Decisions. After being tested partially by using the T-test, the calculated T value is greater than the T table value so it can be concluded that there is a partially significant effect between Service Quality on Staying Guest Decisions. Meanwhile, the calculated F value is greater than the table F value. So it can be concluded that there is a significant influence, namely Online Reviews and Service Quality on Guest Stay Decisions simultaneously. The variable that has a high influence on the decision of the guest to stay in the service quality variable.